'Playing the Chinese card': Globalization and the aesthetic strategies of Chinese contemporary artists. (November 2017) - Zhang, Lin; Frazier, Taj
This article examines the art and travels of two contemporary Chinese artists – Ai Weiwei and Cai Guo-Qiang – to explore how each of them successfully navigates the rapidly shifting terrains and interests of the Chinese state and the global high art industry while simultaneously articulating a distinct politics and practice of creative ambivalence. We argue that these two artists' creative productions and strategies: (1) refute various western critics' critique of Chinese artists as inauthentic imitators of western art who produce exotic representations of China and Chinese identity for western consumption; (2) call into question the Chinese government's numerous efforts to simultaneously promote and control Chinese contemporary art for nationalist/statist purposes. Furthermore, we unpack how both artists deploy various resources to produce complex works that interrogate and demonstrate the clashes of power, culture and identity in global spaces of encounter.